Estudo da soldagem MIG/MAG aplicada a reparo dos aços Cr-Mo e Cr-Mo-V utilizando a técnica de deposição controlada com dupla camada - Pinheiro, Pedro Helton Magalhães (2017)
CrMo and CrMoV alloys steels are widely used for manufacturing of equipment for oil refining and by-products. Operation cycles for those equipment (coke vessels and hydrotreatment reactors, for example) occur in severe conditions, such as high temperature and pressure levels, as well as the presence of hydrogen. Coke vessels are usually produced with ASTM A387 Gr11 steel (CrMo steel) while hydrotreatment reactors are composed by ASTM A387 Gr22 (CrMo steel) along with ASTM A542 Type D (CrMoV steel). Due to wear problems caused by continuous exposure to those conditions, at certain moments of a given equipment’s lifetime, welding repair procedures are required, in order to recover dimentions and restore important properties such as corrosion resistance, assure operational safety and guarantee product quality. However, maintenance interventions represent significant costs, provided specially due to the post weld heat treatment (PWHT) requested in international standards. The application of special welding techniques to provide final microstructure and properties/mechanical properties are very interesting and have a great attractiveness an adequate parameter selection for the welding of two layers with no need for PWHT is of great importance not only from a scientific and technological point of view but also because of its industrial applications. However, the use of alternatives techniques in order to avoid PWTH in repair applications is not simple and not always follow some defined criteria, being based on preliminary experimentation which simulate industrial conditions. Therefore, the main objective of this study is to evaluate the effect of GMAW welding of CrMo and CrMoV steels using the Controlled Deposition Technique with Double Layer for similar (base metal) and dissimilar (coating) repair welding considering the main metallurgical transformations and property changes. The Controlled Deposition Technique with Double Layer was used to obtain the best combinations of welding parameters and techniques in order to reduce hardness and produce the CGHAZ of the first layer grain refinement. The choice of heat imput combinations was based on the Decision Diagram built from microstructure and micro hardness criteria. The approved samples welded with double layer presented acceptable hardness and grain refinement levels. Disapproved samples presented high hardness levels in the HAZ together with grain growth. The prototype electrode (CrMoV) has shown good operational characteristics in welding, although the weld metal’s properties did not meet the toughness requirements. The welds simulating ASTM A387 Gr11 and Gr22 repair achieved excellent results in the HAZ, which means the procedure actually has potential for industrial repair application. Further investigation is required in order to improve the properties obtained for dissimilar welding repair of the ASTM A542 Type D steel. The improvement of the similar welding would be allowed by the development of new consumables, able to provide adequate mechanical properties, according to the current standards.